Choline reverses scopolamine-induced memory impairment by improving memory reconsolidation - Blake, Mariano Guillermo (2012)
It is widely known that pre-training systemic administration of the muscarinic antagonist scopolamine (SCP) (0.5 mg/kg, i.p.) leads to anterograde memory impairment in retention tests. The administration of the α7-nicotinic receptor agonist choline (Ch) in the dorsal hippocampus (0.8 μg/hippocampus) immediately after memory reactivation allowed recovery from scopolamine-induced memory impairment. This effect of Ch was time-dependent, and retention performance was not affected in drug-treated mice that were not subjected to memory reactivation, suggesting that the performance effects are not due to non-specific effects of the drug. The effects of Ch also depended on the age of the reactivated memory. Altogether, our results suggest that Ch exerts its effects by modulating memory reconsolidation, and that the memory impairment induced by low doses of SCP is a memory expression failure and not a storage deficit. Therefore, reconsolidation, among other functions, might serve to change memory expression in later tests. Summarizing, our results open new avenues about the behavioral significance and the physiological functions of memory reconsolidation, providing new strategies for recovering memories from some types of amnesia.